Spatial Analysis of Suicides in the Governorates of Iraq for 2022 Using ArcGIS Pro - Jaleel, Qusai N.; Mohammed, Mohammed A.; Hammadi, Mustafa E.; Hayif, Mustafa Bahaaldin (Iraqi Journal of Science, 2026)
Suicide attempts are a severe global public health concern; suicide patterns might vary based on individual features, techniques, causes, geographical area, and socio-cultural milieu. Suicide rates in Iraq and throughout the world differ significantly by geography. ArcGIS Pro software was used for spatial analysis of the number of suicide cases. Data was collected from the Iraqi Supreme Judicial Council. This study intended to explore spatial patterning and governorate variations in suicide mortality by gender across 15 governorates of Iraq, except for the Kurdistan provinces, between  2017 and 2021, increasing the number of cases by an estimated percentage of 187%. The Suicide Index to 1.409 suicides per hundred thousand people, and the percentage of men who committed suicide was higher than women's suicide rate increased from 96 men and 82 women in 2017 to 286 men and 225 women in 2022; that was based on suicide sites distributed in the governorates of Iraq from the statistics of the Iraqi Ministry of Health. It was found that the Maysan governorate for the year 2022 had the most suicides at 4.6, while the lowest governorate was Anbar at 0.15. The benefit of the study maps designed in the results is to develop planning policies that are appropriate to the location, aimed at mitigating suicide attempts in the governorates of Iraq.